Designing straight-bladed vertical axis wind turbine using the cascade theory - Islam, Mazharul; Amin, M. Ruhul; Carriveau, Rupp; Fartaj, Amir (American Institute of Aeronautics and Astronautics (AIAA), 2008)
In this paper, a 1 kW straight-bladed vertical-axis Darrieus wind turbine is designed using the cascade theory. The effects of dynamic stall and flow curvature, in addition to solidity, design power coefficient, design tip speed ratio, design wind speed, cut-out speed, and blade supporting type (simple, overhang), have been considered. For the performance prediction of Darrieus turbines, especially for the local forces, there appear to be substantial differences between the measured and calculated values unless the dynamic stalling effect is included. For the high chord-radius ratio Darrieus wind turbines, the flow on the blade aerofoil appears to be of curvilinear nature and hence; it is also important to include the flow curvature effect. It has been discovered from the design analyses that the simple supported straight-bladed vertical-axis Darrieus wind turbine is less efficient than the overhang supported turbines. Unlike the other existing theories developed for performance prediction of straight-bladed vertical axis wind turbines, the Cascade Theory with dynamic stall and flow curvature effects does not create a convergence problem for any tip speed ratio and solidity. It has been observed from the design analysis that inclusion of the dynamic stall and flow curvature effects offers better prediction values for different design features, especially in the higher solidity ratios